2020
DOI: 10.3389/fmicb.2020.608380
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of a Trichinella Spiralis Paramyosin-Derived Peptide Modified With a Membrane-Targeting Signal in Mice With Antigen-Induced Arthritis

Abstract: Helminth-derived molecules have the ability to modulate the host immune system. Our previous study identified a tetradecapeptide derived from Trichinella spiralis paramyosin (Ts-pmy) that could bind to human complement component C9 to inhibit its polymerization, making the peptide a candidate therapeutic agent for complement-related immune disorders. Here, the peptide underwent an N-terminal modification with a membrane-targeting signal (a unique myristoylated peptide) to improve its therapeutic efficacy. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“… Chen et al (2020) identified a 14-amino acid peptide derived from Ts-Pmy which was further modified with a membrane-targeting signal to increase its retention time in the joint cavity and enhance its ability to inhibit complement activation. Intra-articular injection of the modified peptide markedly ameliorated knee swelling.…”
Section: Trichinella -Derived Molecules: a Panacea For Moder...mentioning
confidence: 99%
“… Chen et al (2020) identified a 14-amino acid peptide derived from Ts-Pmy which was further modified with a membrane-targeting signal to increase its retention time in the joint cavity and enhance its ability to inhibit complement activation. Intra-articular injection of the modified peptide markedly ameliorated knee swelling.…”
Section: Trichinella -Derived Molecules: a Panacea For Moder...mentioning
confidence: 99%
“…In an effort to identify the effective components in the nematode-secreted proteins that play immunomodulatory functions in host immune systems, it was found that paramyosin as a structural protein expressed on the surface and secreted products of T. spiralis larval and adult worms (TsPmy) is one of the major proteins involved in the immunomodulation of the host immune response through binding to human complement C1q (Sun et al, 2015;Wang et al, 2018) and C8/C9 (Zhang et al, 2011;Zhao et al, 2014) to inhibit complement response. The C9 binding domain of rTsPmy coupled with a membrane-bound signal reduced complement-related arthritis in a mouse model (Chen et al, 2020). Also, rTsPmy was able to activate systemic Tregs and induce the differentiation of Tregs through tolerogenic DCs (Guo et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, TsCRT-S was able to inhibit neutrophil activation as well as formation of ROS and neutrophil NETs in vitro. The authors suggest a potential therapeutic effect of TsCRT-S in the treatment of C1q/immune complex-related autoimmune and inflammatory diseases (1).…”
Section: Editorial On the Research Topic The Role Of Complement In MImentioning
confidence: 99%